Does tillage system affect agricultural production and farmers’ incomes? Evidence from 234 typical farms in 29 countries - Wang, Jiamei; Zhou, Hui; Hu, Xiangdong (Frontiers in Sustainable Food Systems, 2025)
Investigating the impact of tillage system on agricultural production and farmer income, particularly in the face of global threats to food security and adverse environmental conditions, holds considerable importance for guiding policy formulation. This study employs a stochastic frontier analysis to estimate the technical efficiency of wheat production, utilizing data from 234 typical farms across 29 countries for the period 2012–2022. The technical efficiency range for wheat production varies from 0.257 to 0.976, with an average value of 0.830. Additionally, the impact of tillage system on technical efficiency and grain revenue is examined using propensity score matching. The findings indicate that there is no significant difference in technical efficiency between conservation tillage and traditional tillage. Furthermore, compared to conservation tillage, traditional tillage leads to higher grain revenue. Policymakers should evaluate technological adoption comprehensively, considering economic, social, and environmental aspects. Special attention should be directed toward assessing the economic benefits for farmers.